Zwei Ernten später – der Ukrainekrieg und seine Folgen für die globale Versorgung und die europäische Agrar- und Ernährungspolitik - Christine Wieck; Kristina Mensah; Sebastian Hess (Wirtschaftsdienst, 2024)
– Since the coronavirus pandemic and Russia's war of aggression against Ukraine, faltering globalisation and logistics problems have been challenging the agricultural and food industry. EU production and trade developments are presented and the possible consequences for EU agricultural policy are discussed. The article analyses whether the policy changes sought so far through the Green Deal and the 'Farm to Fork' strategy offer the right approaches or whether a rebalancing of objectives is unnecessary, taking into account the planetary boundaries, in order to better examine volume availability, volatility and uncertainty in global agricultural markets.
Keywords: Q18; Q13; Q17; 330; Agrarpolitik; Ernährungspolitik; EU-Staaten; Agrarpolitik; Ernährungspolitik; EU-Staaten